Phenomenology of Vector-like Fermions in Physics Beyond the Standard Model - Cano, Victor Manuel Peralta (2017)
The Standard model of particle physics provides a successful theory to understand the experimental results of the electroweak and strong interactions. However, it does not have a satisfactory explanation for the hierarchy problem. Many extensions of the Standard Model that solve the hierarchy problem result in new particles. We will study the phenomenology of vector-like fermions resulting in theories where the Higgs boson is typically a pseudo-Nambu-Goldstone boson. In these theories we study the case where a heavy fermion will be heavier than a heavy gluon, and then the channel of a heavy fermion decaying into a color octet is considered. We study this phenomenology at high energy colliders, both the LHC as well as future machines.